Pengaruh Pendekatan Pembelajaran Inkuiri Terbimbing Terhadap Hasil Belajar Fisika Peserta Didik Kelas X SMA Negeri 9 Makassar - Wahid, Syamsul (Universitas Mandiri, 2024)
This research was done to know: (1) The physics achievement of 10th grade students in senior high school 9 Makassar that taught by Guided inquiry learning approach. (2) The physics achievement of 10th grade students in senior high school 9 Makassar that taught by conventional teaching approach. (3) The differences of physics achievement in senior high school 9 Makassar between the students that taught by guided inquiry learning approach and the students that taught by conventional teaching approach. This research is a real experiment that uses Posttest Only Control Design. The population in this research is the students of class 10th in Senior High School 9 Makassar. Based on the descriptive analysis showed that the average score of physics achievement of students that taught using guided inquiry approach is27.03 and its deviation standard is 3.32 while the average score of physics achievement that taught without a guided inquiry earning approach is 25.62 and its deviation standard is 3.28. The results of inferential analysis showed that there is a difference between physics achievement of students that taught by guided inquiry approach to learning and the students that taught without guided inquiry learning approach with the real level α = 0.05.